2021
DOI: 10.3390/toxins13100711
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxic Effects Induced by Microcystins and Cylindrospermopsin: A Review

Abstract: Cyanotoxin occurrence is gaining importance due to anthropogenic activities, climate change and eutrophication. Among them, Microcystins (MCs) and Cylindrospermopsin (CYN) are the most frequently studied due to their ubiquity and toxicity. Although MCs are primary classified as hepatotoxins and CYN as a cytotoxin, they have been shown to induce deleterious effects in a wide range of organs. However, their effects on the immune system are as yet scarcely investigated. Thus, to know the impact of cyanotoxins on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 128 publications
0
9
0
Order By: Relevance
“…Although the effects of CYN on the immune system have been scarcely studied, it is known that it can cause immunotoxic effects in in vitro and in vivo models [2,29,30]. In this study we show for the first time the immunotoxic effects that pure CYN can cause in male and female rats orally exposed by repeated doses for 28 days to 18.75, 37.5, or 75 µg CYN/kg b.w./day, following the OECD 407 guideline [37].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the effects of CYN on the immune system have been scarcely studied, it is known that it can cause immunotoxic effects in in vitro and in vivo models [2,29,30]. In this study we show for the first time the immunotoxic effects that pure CYN can cause in male and female rats orally exposed by repeated doses for 28 days to 18.75, 37.5, or 75 µg CYN/kg b.w./day, following the OECD 407 guideline [37].…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the microstructure of the jejunum was destroyed and expression levels of inflammation-related factors IL-1β, IL-8, TNF-α, and IL-10 were altered at different MC-LR concentrations. In fish, however, the number of available studies is higher [30]. The general trend for these studies is an immune-stimulative response at low MC concentrations and an immunosuppressive answer at high MC levels.…”
Section: Gene Expression Analysis Of Ils By Rt-qpcrmentioning
confidence: 99%
See 2 more Smart Citations
“…The main genera producing toxins are Aphanizomenon, Cylindrospermopsis, Dolichospermum (previously Anabaena), Lyngbya, Microcystis, Nostoc, and Planktothrix [63]. These compounds differ in chemical structure (alkaloids, lipids, or cyclic peptides) and toxic effects (cytotoxic, dermatotoxic, hepatotoxic, and neurotoxic effects [64][65][66][67]. The cyclic peptides include microcystins and nodularins, while the alkaloids comprise anatoxin-a, anatoxin-a(S), cylindrospermopsin, saxitoxins (STXs), aplysiatoxins, and lyngbyatoxin [60].…”
Section: Toxinsmentioning
confidence: 99%